Presence of dengue virus RNA in urine and oral fluid of laboratory-confirmed dengue patients: Implications for wastewater surveillance - Christine Stauber; Leile Camila Jacob-Nascimento; Caroline Grosch; Moisés da Silva Sousa; Moyra M. Portilho; Rosângela O. Anjos; Margo A. Brinton; Uriel Kitron; Mitermayer G. Reis; Guilherme S. Ribeiro (Brazilian Journal of Infectious Diseases)
Introduction: Dengue cases in the Americas in 2024 have reached record highs, especially in Brazil. However, surveillance remains suboptimal and new methods are needed to monitor Dengue Virus (DENV) spread. To assess whether wastewater-based epidemiology would be a useful tool, we investigated the presence of DENV RNA in dengue patients’ urine and oral fluid from an endemic area to inform how shedding in these fluids occurs and provide insight for wastewater surveillance. Methods: We examined how often DENV RNA is detected in urine and oral fluid from dengue patients confirmed by serum RT-qPCR, NS1 ELISA or IgM seroconversion in Salvador, Brazil. Results: Of 88 confirmed cases, 9.1 % were positive for DENV RNA in urine (7/88) or oral fluid (1/88). Of 53 serum RT-qPCR-positive patients, 6 (11.3 %) showed detectable DENV RNA in acute- or convalescent-phase urine. Patients with RT-qPCR-positive urine had a lower frequency of DENV IgG in acute-phase serum (a proxy for secondary infection) (57 % vs. 74 %) and a lower median serum RT-qPCR cycle threshold than those with negative urine (21.8 vs. 23.9). Conclusion: The low presence of DENV RNA in urine suggests that additional research is needed to evaluate whether using wastewater-based epidemiology to monitor DENV transmission is possible.